Measuring the quality of melanoma surgery – Highlighting issues with standardization and quality assurance of care in surgical oncology. Issue 3 (March 2017) - Pasquali, S.; Sommariva, A.; Spillane, A.J.; Bilimoria, K.Y.; Rossi, C.R.
Abstract: In an attempt to ensure high standards of cancer care, there is increasing interest in determining and monitoring the quality of interventions in surgical oncology. In recent years, this has been particularly the case for melanoma surgery. The vast majority of patients with melanoma undergo surgery. Usually, this is with combinations of wide excision, sentinel lymph node biopsy and lymphadenectomy. The indications for these procedures evolved during a time when no effective systemic adjuvant therapy was available, and whilst the rationale has been sound, the justification for differences in extent and thoroughness has generally been supported by inadequate or low-level evidence. This has led to a substantial variation among melanoma centres or even among surgeons within a centre in how these procedures are done. With recent rapid progress in the efficacy of systemic treatments that are impacting on overall survival, the prospect of long-term survival in these previously high risk patients means that more than ever long-term locoregional control of melanoma is imperative. Furthermore, the understanding of effects of systemic therapy on locoregional disease will only be interpretable if surgeons use standardized, high quality techniques. This article focuses on standardization and evolution of quality indicators for melanoma surgery and how these might have a positive impact on patient care.